KEPEMIMPINAN TRANSFORMASIONAL DALAM PENGELOLAAN ADMINISTRASI SEKOLAH DI MAS MATHLA"™UL ANWAR PONTIANAK - Yanto, Ari; Sukmawati, Sukmawati; Radiana, Usman (Jurnal Kajian Pembelajaran dan Keilmuan, 2024)
School administration is a process of cooperating with existing resources. Transformational leadership is a leader who has a vision and mission for the future and influences the people he leads to make rapid changes. This study aims to describe transformational leadership in managing school administration at MAS Mathla'ul Anwar Pontianak. The form of research is qualitative with a qualitative descriptive approach. Methods of data collection through interviews, observation, and documentation. The data analysis process implements the Miles and Huberman model, namely data analysis is carried out sequentially starting with data reduction, data exposure, and verification or conclusions. Data validity checking techniques use triangulation and member checks. The findings in this study (1) Charismatic style influences madrasa residents in managing school administration. (2) Inspirational style is capable of directing teachers and administrative staff to achieve common goals. (3) The style of attention makes the madrasa a place for self-actualization. (4) The style of intellectual stimulus encourages madrasa residents to think critically and creatively. The conclusions of this study (1) Charismatic style is able to direct madrasa residents. (2) Inspirational style is able to inspire madrasa residents. (3) The individual attention style of the leadership gives individual attention to the madrasah members. (4) The intellectual stimulus style is able to stimulate madrasa residents in managing school administration.